Effectiveness wall mounted automatic toothbrush against oral hygiene on cerebral palsy children at SMPLB and SMALB D YPAC Jember - Husna Afifah; Dwi Prijatmoko; Kiswaluyo kiswaluyo (Journal of Dentomaxillofacial Science, 2019)
Objective:Cerebral palsy (CP) is a postural syndrome and non-progressive motor disorder due to pyramida and extrapyramidal tract damaged that causes limited motor activity and often accompanied by cognitive impairment or visual deï¬cits. Limited motor activity causes the process of brushing teeth to be hampered so that oral hygiene becomes low. Nowadays there many types of toothbrushes that required diï¬ƒcult motor activities so it is not eï¬€ective for children with CP. Wall Mounted Automatic Toothbrush with an automation system es expected to help CP children maintained their oral hygiene.Material and Methods:This study was clinical experimental with one group pretest posttest design in 5 samples in SMPLB and SMALB DYPAC Jember. Data analysis was the One Way Anova and Post-Hoc test using the Least Signiï¬cat Diï¬€ferent. The Material of this study is wall mounted automatic tootthbrush and manual toothbrush, both of them is used by children with cerebral palsyResults:There are signiï¬cant diï¬€erences between all treatment groups. The lowest of Silness and Loe plaque index of all treatment groups is the treatment group after brushing teeth with manual toothbrush. Conclusion:The conclusion of this study is wall mounted automatic toothbrush can improve oral hygiene measured by the Silness and Loe plaque index.